Hierarchical Control and Optimum Firm Size - Williamson, Oliver E. (Journal of Political Economy, 1967)
There is a great deal of evidence that almost all organizational structures tend to produce false images in the decision-maker, and that the larger and more authoritarian the organization, the better the chance that its top decision-makers will be operating in purely imaginary worlds. This perhaps is the most fundamental reason for supposing that there are ultimately diminishing returns to scale.